Holistic English Mid-Term Assessment for Junior High Schools - Ika Fathin RestiMartanti (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2015)
Assessment is one of integrated parts in teaching and learning process. Due to the change of curriculum in Indonesia, the assessment type which the teachers should use to assess their students is different. According to Curriculum 2013, teachers need to assess every student thoroughly, including their knowledge, skills, and attitudes. In fact, teachers still find difficulties in assessing their students. This phenomenon also happens to the teachers of junior high schools. This research aims to develop a mid-semester assessment model which is more practical and less time-consuming for English teachers in junior high schools. The method was Research and Development (RD). The data were collected from group discussion, questionnaires, and interviews. The result of the research is a holistic English assessment model which can be used for a mid-semester period. A holistic assessment covers the partial and contextual aspects of teaching and learning. It consists of two types: student assessment and portfolio assessment. This assessment model is expected to improve the effectiveness of the assessment technique for junior high schools and to provide more opportunities for teachers to conduct the mid-term assessment which is not really taken into account as a part of classroom activities.